Shedding Light on the Management of School Operational Assistance (SOA) Fund Effectiveness: a Case Study of State Basic Education Level in Demak Regency - Tegar Putra Wijayanto; Agus Sunarya Sulaeman; Ryan Nugraha (Ilomata International Journal of Social Science, 2022)
School Operational Assistance (SOA) Fund is one of the educational funds in Indonesia. Based on the APBN Financial Note, the management of the SOA fund is still not optimal, and there are still many misuses of the SOA fund by various parties. Therefore, it is necessary to apply the good governance principles in the management of the SOA fund. This study aims to analyze the effectiveness of the management of the SOA fund, which is influenced by good governance, namely transparency, accountability, participation, and responsibility. The object of this study is the management of the SOA fund at the level of state basic education in Demak Regency, which consists of State Elementary Schools and State Junior High Schools. The data source of this research is primary data using a questionnaire. There are 494 respondents in this research. The respondents are headmasters, school treasurers, teachers, and other parties in school. The study results show that the SOA fund at the level of state basic education in Demak Regency has been managed effectively. The study results also show that all independent variables simultaneously have a positive effect on the effectiveness of the management of the SOA fund. Partially, transparency does not affect the effectiveness of SOA fund management, while accountability, participation, and responsibility have a positive effect on the effectiveness of the management of SOA fund.